To Find a Standard Format That Measures the Activities of a Micro, Small or Medium Business Entity. A Pitch - Peter Ellis (Journal of Accounting and Management Information Systems (JAMIS), 2016)
This pitch is a proposed strategy for my current research which is to identify, examine and understand the essential elements that identify Micro, Small and Medium Enterprises (MSMEs) as unique identities within the field of business management. I shall be using the format developed by Faff (2015b) for novice pitchers and (Faff, 2015a), which establishes the academic existence of the template tool. Using this tool I am discussing the motivation and puzzle, followed by introducing the idea, data and tools that are used. I then explain what is new and the benefit of the use of the new data, finally presenting a conclusion that offers the contribution and other considerations. The Pitch is a direct result of completing a course set out by Professor Faff RBUS6914 "The (Academic) research Process".
Keywords: M19; 650; Pitching research; Definition of Micro; Small and Medium Enterprises (MSMEs) studies; Business stability within size parameter; Comparative studies; Decision making